2005
DOI: 10.5424/srf/2005143-00920
|View full text |Cite
|
Sign up to set email alerts
|

Molecular responses to thermal stress in woody plants

Abstract: Stress caused by high and low temperatures has been much less studied in woody plants than in herbaceous ones. The cold response shows specific traits in woody plants. Cold acclimation associated to winter dormancy develops in two sequential steps: the first is triggered by photoperiod shortening while the second requires temperatures to fall. The involvement of ABA in cold acclimation is beyond question, yet the roles played by this hormone are far better understood in herbaceous plants. The induction of prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 113 publications
0
4
0
Order By: Relevance
“…Although certain groups were more abundant, it does not necessarily indicate the importance of one group over another. Genes corresponding to cell defence included known antifreeze genes, such as dehydrins and pathogenesis-related genes like IV chitinase, b-1-3-glucanase and thaumatin-like genes (reviewed by Gómez et al 2005;Joosen et al 2006). Furthermore genes encoding HSPs were induced in response to cold stress.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although certain groups were more abundant, it does not necessarily indicate the importance of one group over another. Genes corresponding to cell defence included known antifreeze genes, such as dehydrins and pathogenesis-related genes like IV chitinase, b-1-3-glucanase and thaumatin-like genes (reviewed by Gómez et al 2005;Joosen et al 2006). Furthermore genes encoding HSPs were induced in response to cold stress.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this included also genes of which it is known that they function in hormonal signal transduction pathways, such as the abscisic acid (ABA) transduction pathway. Biochemical and genetic studies in the past have shown that ABA is increased when exposed to a low temperature and triggers processes leading to increased frost tolerance (Marek et al 1992; reviewed by Gómez et al 2005;Joosen et al 2006). Cell wall modification is necessary to protect the cell against freeze-induced stress.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations